IMPROVEMENT OF CAPITAL MANAGEMENT POLICY AT THE ENTERPRISE - TITENKO, Zoia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article substantiates that capital is the most important economic category for the creation and development of an enterprise. It is the main factor of production that allows an enterprise to carry out production processes, invest in development, acquire necessary resources and introduce new technologies. Capital also characterizes the financial resources of the enterprise, its financial stability and development opportunities. In addition, capital plays an important role in satisfying the interests of the state, which regulates its use, in particular through taxation of profits, owners who invest in the enterprise and expect profits, and personnel who receive wages and social guarantees. Capital acts as a key element in the functioning and development of any business entity. It is also actively determined that the development of a system of effective capital management is of great importance in modern conditions of conducting economic activity. The process of capital management is one of the key aspects of the successful operation of any enterprise.The capital management process is one of the key aspects of the successful operation of any enterprise. Effective capital management helps to ensure the optimal use of financial resources, which allows the enterprise to achieve maximum efficiency and profitability. In addition, proper capital management helps to reduce the risks of capital investment, assess and control financial risks, and rationally allocate resources to achieve the strategic goals of the enterprise. Capital management plays an important role in increasing profitability and increasing the financial performance of the enterprise. However, it is true that this aspect is often not given enough attention. Usually, attention is focused on capital allocation during annual budgeting, focusing mainly on financing specific projects, rather than on capital management strategies as a whole. It is important to consider that effective capital management involves not only the allocation of funds, but also strategic planning, optimization of resources and maximization of profitability in the long term.
Keywords: capital; management; planning; financial resources; performance